2021
DOI: 10.1186/s12961-020-00644-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the theory, barriers and enablers for patient and public involvement across health, social care and patient safety: a systematic review of reviews

Abstract: Background The emergence of patient and public involvement (PPI) in healthcare in the UK can be traced as far back as the 1970s. More recently, campaigns by harmed patients have led to a renewed focus on strengthening PPI. There is a growing awareness of the benefits of PPI in research as well as a need to address power inequities and a lack of diversity and inclusion. This review was undertaken to look at evidence for theories, barriers and enablers in PPI across health, social care and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
207
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(253 citation statements)
references
References 63 publications
11
207
1
1
Order By: Relevance
“…These challenges were recognised by our co-researchers and also within the wider literature [ 53 ]. Although it remains the case that it is less common for researchers to report the challenges of PPI in research, or the wider systems within which it operates [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These challenges were recognised by our co-researchers and also within the wider literature [ 53 ]. Although it remains the case that it is less common for researchers to report the challenges of PPI in research, or the wider systems within which it operates [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our PPIE collaborators made valuable contributions to, and provided insights into, each work package, enabling us to develop recommendations for delivering future PPIE work. Issues to be considered in future PPIE activities described by the group included: retention of PPIE contributors; diversity; inclusion; choice of language; and measuring fear, or the stigma of becoming involved in PPIE activities(18,19,(69)(70)(71). We recommend linking to external organisations who embed PPIE work at the heart of research, such as the NIHR (3), and the National Co-ordinating Centre for Public Engagement (NCCPE: (72)), where guidance is kept current, to encourage a culture of fair, equitable and meaningful involvement.…”
mentioning
confidence: 99%
“…Prior research that referred to PE largely focused on engaging individuals in their own clinical care or as members of research teams 16,17 . Other research on PE in health‐care organizations was conducted in the primary care context, revealing numerous barriers 4‐6 . Little prior research examined organizational PE in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review (11 studies 2003‐2012) found that patients were typically consulted after decisions had been made, which did not lead to improvements 5 . More recently, a systematic review of 42 reviews (up to 2018) identified numerous organizational barriers of PE: knowledge, attitudes, expectations, communication, financing, resourcing, training, patient/family recruitment and representation, and addressing power dynamics 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation